(untitled) (Al-Qamar, 2022)
The important role of women in reforming the society and keeping it on the right path cannot be denied. For the betterment of the society, apart from Hazrat Adam, as many Prophets as came, scholars, peacemakers, elders of religion, heads of nations, those who played a significant role in courage and bravery, all of them were born from a respected woman. Their mother’s embrace was their first teacher and first school. The credit for all the achievements of the best goes to their first education. Therefore, the Prophet ﷺ has said in view of the importance of women; "The most valuable thing in the world is a good woman, by her goodness the world becomes good." The people of the West and Europe are constantly criticizing the people of Islam that Islam is unable to give women their real importance. Keeping the same thing in mind, the writer raised her pen and the analytical text was brought forward.